2022
DOI: 10.3390/biology11071009
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Phase Transition in Neurodegenerative Diseases by Nuclear Import Receptors

Abstract: RNA-binding proteins (RBPs) with a low-complexity prion-like domain (PLD) can undergo aberrant phase transitions and have been implicated in neurodegenerative diseases such as ALS and FTD. Several nuclear RBPs mislocalize to cytoplasmic inclusions in disease conditions. Impairment in nucleocytoplasmic transport is another major event observed in ageing and in neurodegenerative disorders. Nuclear import receptors (NIRs) regulate the nucleocytoplasmic transport of different RBPs bearing a nuclear localization si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 289 publications
(395 reference statements)
0
8
0
Order By: Relevance
“…The discovery that NIRs counter deleterious phase transitions of RBPs has led to the idea that NIRs can be utilized for therapeutic applications to restore RBP homeostasis and mitigate neurodegeneration [ 14 , 15 , 17 , 18 , 42 , 142 ]. It is unclear why TNPO1 accumulates in FUS-positive inclusions in FTLD-FUS rather than preventing FUS aggregation, since TNPO1 can efficiently reduce phase separation of hypomethylated FUS in vitro and in cells [ 40 , 49 ].…”
Section: Therapeutic Potential Of Nirs Countering Aberrant Phase Tran...mentioning
confidence: 99%
“…The discovery that NIRs counter deleterious phase transitions of RBPs has led to the idea that NIRs can be utilized for therapeutic applications to restore RBP homeostasis and mitigate neurodegeneration [ 14 , 15 , 17 , 18 , 42 , 142 ]. It is unclear why TNPO1 accumulates in FUS-positive inclusions in FTLD-FUS rather than preventing FUS aggregation, since TNPO1 can efficiently reduce phase separation of hypomethylated FUS in vitro and in cells [ 40 , 49 ].…”
Section: Therapeutic Potential Of Nirs Countering Aberrant Phase Tran...mentioning
confidence: 99%
“…, TDP-43). For example, the study from Girdhar and colleagues identified an acridine derivative, that is, AIM4, as an anti-TDP-43 aggregation molecule that binds to TDP-43 disordered region ( 154 , 156 ). A third way is the use of drugs that target mediators influencing LLPS such as post-translational modifications of proteins or the epigenetic state of DNA and RNA, which are both essential for the nucleation of condensates ( 157 , 158 ).…”
Section: Targeting Condensate Formation In Ddr: a Novel Perspective T...mentioning
confidence: 99%
“…Due to their biomolecular properties, R-DPRs have been demonstrated to undergo LLPS [reviewed elsewhere (Mann and Donnelly, 2021 ; Solomon et al, 2021 ; Yoshizawa and Guo, 2021 ; Girdhar and Guo, 2022 )], a process in which proteins demix from aqueous solutions into liquid-like droplets (also referred to as condensates), which under abnormal conditions can mature into less dynamic fibrillar/aggregate-like structures, potentially underlying protein aggregation in neurodegenerative diseases. LLPS (also referred to interchangeably as condensation) is a fundamental property of many proteins containing disordered domains (such as FG-Nups) and RNA binding proteins (such as TDP-43, FUS, and stress granule protein G3BP1), and is crucial for many biological processes.…”
Section: Abnormalities Of the Npc In C9orf72 -Alsmentioning
confidence: 99%